2015
DOI: 10.1177/1352458515578771
|View full text |Cite
|
Sign up to set email alerts
|

miRNA in multiple sclerosis: search for novel biomarkers

Abstract: A major challenge in multiple sclerosis (MS) is to develop biomarkers that could help in understanding individual MS patients, i.e. whether they are a responder or non-responder to therapy, which medicine is more effective, and the degree to which they may be entering the progressive phase of disease. In the last few years, a lot of attention has been drawn toward identification of diagnostic, prognostic, process-specific, and treatment-related biomarkers for MS. In this review, we will focus on the micro RNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 51 publications
1
52
0
Order By: Relevance
“…MicroRNAs have been proposed as biomarkers relevant to diagnosis, stage of disease, and response to treatment in MS. 3335,53 Magnetic resonance imaging techniques have long contributed to the diagnosis and monitoring of the disease. 3 Imaging advances have allowed measurement of heterogeneous pathologic processes, allowing clustering of patients based on these differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MicroRNAs have been proposed as biomarkers relevant to diagnosis, stage of disease, and response to treatment in MS. 3335,53 Magnetic resonance imaging techniques have long contributed to the diagnosis and monitoring of the disease. 3 Imaging advances have allowed measurement of heterogeneous pathologic processes, allowing clustering of patients based on these differences.…”
Section: Discussionmentioning
confidence: 99%
“…3033 Previous studies have also shown associations between MS disability or disease progression and the expression of miRNAs. 34,35 …”
mentioning
confidence: 99%
“…Previous reports of miRNA modulators of both neuronal and immune processes (also termed as NeurimmiRs [36]) predicted therapeutic potential for manipulating miRNA levels in diseases affecting both the immune system and higher brain functions, such as AD [37], Parkinson's disease (PD) [38], multiple sclerosis (MS) [39], anxiety-related disorders [40] and epilepsy [41]. miRNAs primarily target transcriptional or other regulatory genes, which enable modulation of both immune and cognitive processes through direct or indirect alterations of glia-neuron signalling.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the most abundantly studied class of these exRNAs are microRNAs (miRNA), which have been implicated in a wide range of diseases including heart failure [1, 2], cancer [3, 4], and multiple sclerosis [5, 6]. miRNAs are small, non-coding RNAs that have the ability to regulate whole networks of genes through transcriptional and translational regulation.…”
Section: Introductionmentioning
confidence: 99%